Multitrait aposematic signal in Batesian mimicry. (1st July 2016) - Outomuro, David; Ángel‐Giraldo, Pedro; Corral‐Lopez, Alberto; Realpe, Emilio
Abstract: Batesian mimics can parasitize Müllerian mimicry rings mimicking the warning color signal. The evolutionary success of Batesian mimics can increase adding complexity to the signal by behavioral and locomotor mimicry. We investigated three fundamental morphological and locomotor traits in a Neotropical mimicry ring based on Ithomiini butterflies and parasitized by Polythoridae damselflies: wing color, wing shape, and flight style. The study species have wings with a subapical white patch, considered the aposematic signal, and a more apical black patch. The main predators are VS‐birds, visually more sensitive to violet than to ultraviolet wavelengths (UVS‐birds). The white patches, compared to the black patches, were closer in the bird color space, with higher overlap for VS‐birds than for UVS‐birds. Using a discriminability index for bird vision, the white patches were more similar between the mimics and the model than the black patches. The wing shape of the mimics was closer to the model in the morphospace, compared to other outgroup damselflies. The wing‐beat frequency was similar among mimics and the model, and different from another outgroup damselfly. Multitrait aposematic signals involving morphology and locomotion may favor the evolution of mimicry rings and the success of Batesian mimics by improving signal effectiveness toward predators.